Iot-enabled smart healthcare systems, services and applications - Rani, Shalli (John Wiley & Sons, Inc., 2022)
"IoT-enabled healthcare (smart healthcare) has been under development for some time, with some of the first devices being heart monitors that automatically send data to physicians when a key event occurs or at set intervals. Wearable monitors have also offered non-intrusive technologies to enable user participation in healthcare, and easier remote monitoring of conditions. Juniper Research anticipates that the COVID-19 pandemic will accelerate adoption of IoT within the healthcare industry, and issues around security and privacy, handling data sets, reliability of devices and interoperability of systems are already coming to the fore as key challenges. New technologies such as machine learning, image processing, big data, remote monitoring, cloud computing, deep learning, and enhanced wireless communications are all improving and connecting modern healthcare services and products through IoT. https://www.juniperresearch.com/press/press-releases/iot-platform-revenue-to-grow-20-in-2020"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on April 14, 2022)
Keywords: Medical informatics; Médecine; Informatique